The Worst Availability as a Parameter for Designing and Reporting on the Network Performances - Ivan Rados; Ladislav Schwartz (Communications - Scientific letters of the University of Zilina, 2011)
In the introductory part, the reasons why the availability is important are stated as well as the overview of the papers produced so far dealing with the problem of guaranteed availability. Furthermore, the basic concepts on availability are introduced with the special review of the parallel structure which can actually be applied onto the ring network. The principles of protection of the wavelength channel and optical multiplex section which are used in the ring WDM networks are described. Then the availabilities of different link configurations in relation to its protection are defined: without protection, protection using the same optical cable and protection using completely separated optical cables. Then the availability of the WDM ring was analysed which uses protection of the wavelength channel as well as the protection of the optical multiplex section. Furthermore, the expression for the worst availability of the WDM ring was derived and the number of links of the working path which gives the worst availability was determined. The data on the intensity of failures and the mean time to repair of individual components were taken from different literature. In the analysis we assumed that it is about WDM system with 64 wavelengths. At the end of the paper the answer to the question why the worst availability can be taken as a parameter at projecting WDM networks and for the reporting on the network performances was given.